2011
DOI: 10.1007/s00284-011-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

The Proteolytic Activation of the relNEs (ssr1114/slr0664) Toxin–Antitoxin System by Both Proteases Lons and ClpP2s/Xs of Synechocystis sp. PCC 6803

Abstract: The proteolytic regulation of toxin-antitoxin (TA) systems has been well studied in Escherichia coli but remains unclear in other bacteria. A chromosomal gene pair ssr1114/slr0664, named relNEs, of Synechocystis sp. PCC 6803 forms a TA system belonging to rel family. Here, we used E. coli strain BL21 (DE3) as a host to characterize the proteolytic regulation of relNEs. The proteases of this strain could not degrade the antitoxin RelN, and the ectopic production of the ATP-dependant protease Lons or ClpP2s/Xs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…The unicellular cyanobacterium, Synechocystis sp. PCC 6803, contains as many as 34 putative TA systems [15][17], including our previously characterized reNlEs operon [31], [52]. Characterization of this TA system carried out in E. coli demonstrated that the relNEs operon constitutes a “hybrid” TA systems where the toxin gene relEs belonging to the relE family is paired with the antitoxin gene relN with no sequence homology to characterized antitoxin genes [52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The unicellular cyanobacterium, Synechocystis sp. PCC 6803, contains as many as 34 putative TA systems [15][17], including our previously characterized reNlEs operon [31], [52]. Characterization of this TA system carried out in E. coli demonstrated that the relNEs operon constitutes a “hybrid” TA systems where the toxin gene relEs belonging to the relE family is paired with the antitoxin gene relN with no sequence homology to characterized antitoxin genes [52].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the antitoxin protein RelN in E. coli could be degraded by both Lons and ClpP2s proteases from Synechocystis sp. PCC 6803, thus resulting in the activation of the toxin RelEs from the RelN-RelEs complex [31]. Anabaena encodes at least 38 putative type II TA systems [15][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the only cyanobacterial TA system that has been experimentally characterized thus far is the chromosomally located relNE (ssr1114/slr0664) TA system of Synechocystis and its proteolytic regulation by ATP-dependent proteases (16).…”
mentioning
confidence: 99%
“…strain PCC 6803 encodes 62 peptidases (17). Proteolysis in cyanobacteria has been associated with the degradation of a few specific proteins (18)(19)(20)(21)(22)(23)(24) or with stress response pathways (25)(26)(27).…”
mentioning
confidence: 99%